Profile and food safety knowledge of individuals who work in food trucks in a capital in southern Brazil (Research, Society and Development, 2020)
The purpose of the study was to identify the socioeconomic and professional profile of owners and food handlers of food trucks in a capital in the south of Brazil, as well as to evaluate the knowledge of these individuals regarding food safety. A total of 119 individuals in Curitiba, Brazil, participated in the study. For data collection, was elaborated a questionnaire about the socio-demographic, professional profile and food safety knowledge, which was filled by the participants during events. The majority of the individuals were owners (75.63%), of the male gender (69.75%), aged between 30 and 44 years-old (56.30%) and with complete/incomplete higher education (55.46%). The participants answered of the questions of food safety correctly (76.63%). There was a significant difference regarding food safety knowledge among the participants related to the level of education (p=0.0054), length of service in the food segment (p=0.0267), and the completion of courses related to the food area (p=0.0016). These results emphasize the need for continuous education and for the development of new strategies for food safety training, in order to improve the knowledge of street food workers.